DESAIN INDEPENDENSI PERADILAN PAJAK - Hadiyantina, Shinta (JURNAL KONSTITUSI, 2011)
Taxes are very important role in nation-building, because about 70 percent of state revenues derived from taxes. Tax Tribunal established under Law No. 14 of 2002 has put the tax court in a position that is not independent, so a redesign of the existence of absolute tax court diperlukan.Dalam redesign of the tax court to reinforce the position of tax court as a special court under the administrative courts country and be under one roof the Supreme Court